Application of Novel Plasmonic Nanomaterials on SERS - Barbillon, Grégory (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Surface-enhanced Raman scattering (SERS) is a research technique that was discovered in the mid-1970s. SERS is a powerful and fast tool for analysis, which has a high detection sensitivity for a great number of chemical and biological molecules. However, it is in this last decade that a very significant explosion of the fabrication of highly sensitive SERS substrates has occurred using novel designs of plasmonic nanostructures and novel fabrication techniques of the latter, as well as new plasmonic materials and hybrid nanomaterials. Thus, this Special Issue is dedicated to reporting on the latest advances in novel plasmonic nanomaterials that are applied to the SERS domain. These developments are illustrated through several articles and reviews written by researchers in this field from around the world.